North Yorkshire and Its Depiction in the Gothic novel The Woman in Black - Drábková, Natálie (Univerzita Pardubice, 2022)
The bachelor thesis is focused on the analysis of the Gothic novel The Woman in Black by Susan Hill. The main aim of the work is to prove that the novel can be characterized as a Regional and a Gothic novel. The analysis deals with the depiction of Yorkshire and the Humber in the selected novel and aims to discover which Regional and Gothic elements are used in the novel. The thesis also draws attention to the Victorian era and its values reflected in the analysed novel.
Zobrazení Severního Yorkshire v Gotickém románu The Woman in Black od Susan Hillové
Keywords: gothic novel; Susan Hill; regional novel; Yorkshire and Humber; North Yorkshire; Victorian era; gotický román; Susan Hill; regionální román; Yorkshire a Humber; Severní Yorkshire; viktoriánská éra